Winds of change in natural resource governance: Wind power and reindeer husbandry building the just transition together in Northern Finland - Luoma, Emma; Hast, Sanna; Kangasoja, Jonna (Alue ja Ympäristö, 2023)
Finland has a clear strategic goal to significantly increase the share of wind power as part of the green energy transition. The reindeer management area (RMA), which covers more than a third of Finland, is attractive for the development of wind power due to the sparse population and good wind conditions. However, the area holds significant importance in reindeer husbandry practices while being a subject to many other land use pressures which change the possibilities of reindeer herders to operate and use pastures. Wind power lands as a part of a historical continuum, where reindeer herders have had to adjust to various forms of land use. Currently, cumulative effects of these land uses, as well as how and under what conditions the prerequisites for reindeer herding can be secured emerge as key questions for just transition. In this review, we examine the features and legal status of reindeer herding, as well as the challenges arising from increasing wind power production in the RMA. We also discuss possible new practices for the resolution of these challenges and ensuring a fair transition. As a promising example, we describe the on-going collaboration between wind power operators and reindeer husbandry in Finland since 2019. Suomessa on selkeä strateginen tavoite lisätä tuulivoiman osuutta tuntuvasti osana vihreää energiasiirtymää. Reilun kolmanneksen Suomen maa-alasta kattava poronhoitoalue on houkutteleva tuulivoiman kehittämiselle harvan asutuksen ja hyvien tuuliolosuhteiden vuoksi. Poronhoidon näkökulmasta alueet ovat kuitenkin jo käytössä, ja poronhoidon lisäksi alueelle kohdistuu myös monia muita maankäyttöpaineita. Tuulivoiman lisärakentaminen näille alueille muuttaa laidunten käyttömahdollisuuksia ja kaventaa poronhoidon toimintaympäristöä. Tuulivoimahankkeet nivoutuvat osaksi historiallista jatkumoa, jossa poronhoitajat ovat olleet väistäjän ja haitan kärsijän roolissa uusien maankäyttömuotojen viedessä alaa perinteiseltä elinkeinolta. Nykytilanteessa poronhoidon kannalta kyse on kasautuvista ...